2023
DOI: 10.3390/biology12091202
|View full text |Cite
|
Sign up to set email alerts
|

The Long Scientific Journey of Sirolimus (Rapamycin): From the Soil of Easter Island (Rapa Nui) to Applied Research and Clinical Trials on β-Thalassemia and Other Hemoglobinopathies

Roberto Gambari,
Cristina Zuccato,
Lucia Carmela Cosenza
et al.

Abstract: In this review article, we present the fascinating story of rapamycin (sirolimus), a drug able to induce γ-globin gene expression and increased production of fetal hemoglobin (HbF) in erythroid cells, including primary erythroid precursor cells (ErPCs) isolated from β-thalassemia patients. For this reason, rapamycin is considered of great interest for the treatment of β-thalassemia. In fact, high levels of HbF are known to be highly beneficial for β-thalassemia patients. The story of rapamycin discovery began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 115 publications
1
5
0
Order By: Relevance
“…[43]. These data strongly support the concept that sirolimus, in addition to the reported effects on HbF and γ-globin gene expression [35,36,39,43,47], is able to activate programs controlling the excess to α-globin production, ultimately reducing ineffective erythropoiesis. In order to verify whether the sirolimus-mediated effect on AHSP mRNA also occurs in vivo in sirolimus-treated β-thalassemia patients, we took advantage of the clinical trial NCT03877809 (Sirthalaclin).…”
Section: Selected Activities Of the Sirthalaclin Nct03877809 Clinical...supporting
confidence: 69%
See 3 more Smart Citations
“…[43]. These data strongly support the concept that sirolimus, in addition to the reported effects on HbF and γ-globin gene expression [35,36,39,43,47], is able to activate programs controlling the excess to α-globin production, ultimately reducing ineffective erythropoiesis. In order to verify whether the sirolimus-mediated effect on AHSP mRNA also occurs in vivo in sirolimus-treated β-thalassemia patients, we took advantage of the clinical trial NCT03877809 (Sirthalaclin).…”
Section: Selected Activities Of the Sirthalaclin Nct03877809 Clinical...supporting
confidence: 69%
“…Sirolimus (rapamycin) is one of the most promising drugs for inducing HbF [35][36][37][38]] and, at the same time, ULK1-mediated autophagy [19,20]. The several applications of sirolimus in biomedicine, from its discovery to its possible use in clinical trials, have been recently reviewed [39]. Sirolimus was first demonstrated to be a potent anti-bacterial and anti-fungal agent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their data support the concept that autophagy, Ulk1 increased expression, and α-globin chain reduction are activated in β-thalassemia patients who take a daily dosage of 2 mg rapamycin (sirolimus). The experimental evidence and technology-transfer activities sustaining sirolimus-based clinical trials have been recently reviewed [ 101 ]; information on the NCT03877809 clinical trial can be found in Gamberini et al [ 102 ], while the first report on the results of the trial has been published by Zuccato et al [ 103 ]. The main results of the trial, reported by Zuccato et al [ 103 ], were that the content of γ-globin RNA and HbF are increased in ErPCs isolated from sirolimus-treated β-thalassemia patients.…”
Section: The Unc-51-like Kinase 1 ( Ulk1) Gene Pla...mentioning
confidence: 99%